Elementy uzbrojenia i oporządzenia jeździeckiego z nowożytnego dworu w Janiszewie na Kujawach Brzeskich - Poturalska, Ewa (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
In the years 1993-1997 archaeological field works were conducted at site 2 in Janiszewo. The works resulted in uncovering of a rural manor house which presumably functioned since the end of the 14th century until the beginning of the 19th century. Some of the articles found within the confines of the house can be numbered among armament and horseman equipment. We can ennumerate here: an axe, knives, a ball, a crossbow stirrup, a pistol, a spur and a horseshoe. The axe was identified as type IX (according to the typology by M. Glosek) and thereby it can be assumed that this tool was used only on special occasions. Since the axe bears features characteristic both for the period between the first half of the 13th century and the present times and since it was found within the limits of the house yard, its dating is very much limited. Similar problem with accurate dating arises in case of recovered in the same place seventeen knives. Their pommels were from 5 to 15 cm long. Among the knives a fragment of a kitchen chopper was distinguished. An iron ball,17 mm in diameter, was presumably either a musket bullet or a bullet shot from a crossbow. The 16th or 17th century stirrup from a hunting or sports crossbow was helpful not only while tightening the bowstring, but also while hanging the crossbow on the wall. A pistol, with an octahedral 10 mm calibre barrel and a wheel lock, probably belongs to an early form of a pistol, still with a characteristic smooth barrel. Its origin may be dated to the end of the 16th or the beginning of the 17th century. However, the 17th century spur with a star-shaped spike does not fit any of the known spur typologies. A stirrup from the specimen from Janiszewo had been evidently damaged and repaired to be used again. Some of the features of the recovered horseshoe allow to identify it as the type IV, of the II nd group, with the fasteners of type D, according to the typology by J. Kaźmierczyk. The above described finds were presumably used as either military, hunting or sports equipment. Only the destination of the pistol is unquestionable. The present work should be treated as my contribution to the researches on so far vaguely accentuated issue of archaeologically registered home arsenals from the rural manor foundations.